2023
DOI: 10.1002/jmri.28634
|View full text |Cite
|
Sign up to set email alerts
|

Multidelay MR Arterial Spin Labeling Perfusion Map for the Prediction of Cerebral Hyperperfusion After Carotid Endarterectomy

Abstract: BackgroundMultidelay arterial spin labeling (ASL) generates time‐resolved perfusion maps, which may provide sufficient and accurate hemodynamic information in carotid stenosis.PurposeTo use imaging markers derived from multidelay ASL magnetic resonance imaging (MRI) and to determine the optimal strategy for predicting cerebral hyperperfusion after carotid endarterectomy (CEA).Study TypeProspective observational cohort.SubjectsA total of 79 patients who underwent CEA for carotid stenosis.Field Strength/Sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…In this issue, Fan et al 5 report the use of multidelay arterial spin labeling (ASL) perfusion MRI at 3 T to predict radiographic cerebral hyperperfusion following carotid endarterectomy. In 79 patients with moderate‐to‐severe unilateral carotid stenosis who underwent multidelay ASL perfusion imaging before and after carotid endarterectomy, the authors found that multidelay ASL MRI was able to detect radiographic cerebral hyperperfusion, defined as an increase in cerebral blood flow (CBF) of more than 100% compared with baseline preoperative values.…”
mentioning
confidence: 99%
“…In this issue, Fan et al 5 report the use of multidelay arterial spin labeling (ASL) perfusion MRI at 3 T to predict radiographic cerebral hyperperfusion following carotid endarterectomy. In 79 patients with moderate‐to‐severe unilateral carotid stenosis who underwent multidelay ASL perfusion imaging before and after carotid endarterectomy, the authors found that multidelay ASL MRI was able to detect radiographic cerebral hyperperfusion, defined as an increase in cerebral blood flow (CBF) of more than 100% compared with baseline preoperative values.…”
mentioning
confidence: 99%